Dampak Negatif TikTok pada Karakter Anak - Firdiana, Linda; Fatimah, Meti; Subando, Joko (TSAQOFAH, 2026)
The use of the social media platform TikTok is increasingly widespread among children and has become one of the digital platforms that significantly influence their behavior and character development. This article aims to analyze the negative impact of TikTok on children’s character through library research, highlighting the limited number of studies that specifically link TikTok use with children’s character formation. Data were obtained from books, scholarly journals, and research findings related to social media and child development, and were analyzed using a qualitative critical analysis technique. The findings show that TikTok has a significant impact on children’s moral, behavioral, social, and emotional aspects; exposure to age-inappropriate content contributes to decreased politeness, the emergence of negative imitative behaviors, concentration disturbances, and a tendency to seek social validation. In addition, intensive use of TikTok weakens children’s ability to interact in real-life social settings and reduces their emotional stability. This article concludes that guidance, digital supervision, and strengthened character education are necessary so that children can respond to the influence of social media critically and responsibly, while also underscoring the urgency of character education in the digital era as an integral part of parenting and child education.